VARIABILITAS IKLIM DAN KEJADIAN KEBAKARAN HUTAN DAN LAHAN GAMBUT DI KABUPATEN BENGKALIS, PROVINSI RIAU Variability of Climate and Forest and Peat Fires Occurrences in Bengkalis Regency, Riau - Lailan Syaufina; Dinda Aisyah Fadhillah Hafni (Jurnal Silvikultur Tropika, 2018)
Bengkalis is one of the regency in Riau which is vulnerable to forest and peatland fires due to land use change. This research aimed to analyze the distribution of forest and peat fires in Bengkalis, and observe the correlation between climate (rainfall, maximum air temperature, and average air temperature) and hotspot as an indicator of forest and peat fires occurrences in Bengkalis. The climate data derived from Indonesian Agency for Meteorological, Climatological and Geophysics (BMKG) and global climate data from Climatic Research Unit (CRU) satellite. The result revealed that climate patterns of CRU satellite are in line with climate patterns of BMKG observations. Hotspots spatial distribution showed the years of 1998, 2002, 2004, 2005, 2006, and 2009 as years with a high number of hotspots. Most hotspots are found in the peat soil types Hemists/Saprists (60/40), very deep and on land cover shrub swamp. The maximum air temperature and average air temperature showed significant correlation (p-value <0.05) to the number of hotspots while the rainfall did not significantly affect the number of hotspots. The best model illustrated the absence of a suitable model to describe the relationship between climate and the number of hotspots.Key words: climate, Climatic Research Unit, hotspot, peat fires